Chuzhaia strana - Razbezhkina, Marina (Russia : Risk Film Studio, 2004)
Russian Dilara lived with Henrikus Svans for several years in Tilburg, the Netherlands. Henrikus however decided to end the contract of cohabitation with her arguing that she merely used him in order to have legal status in the Netherlands. The film follows their story from the perspective of Dilara, who is now concerned about her options to ensure her and her son’s stay in the country.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films